Improving functional outcomes in early‐stage bipolar disorder: The protocol for the REsearch into COgnitive and behavioural VERsatility trial. Issue 6 (10th February 2019) - Cotton, Sue M.; Berk, Michael; Jackson, Henry; Murray, Greg; Filia, Kate; Hasty, Melissa; Chanen, Andrew; Davey, Christopher; Nelson, Barnaby; Ratheesh, Aswin; MacNeil, Craig
Abstract : Aim: Young people with bipolar disorder (BD) commonly experience reduced quality of life, persistent symptoms and impaired functional recovery despite often superior school performance. Compromised long‐term functioning can ensue. There is evidence that psychological therapies alongside pharmacology may be more efficacious earlier in the course of the disorder. Intervention in the early stages may thus reduce the burden and risk associated with BD and mitigate the impact of the disorder on normal developmental trajectories. To date, however, the availability of evidence‐based psychological therapies for young people with early BD is limited. Furthermore, there are no large‐scale randomized controlled trials (RCTs) of such interventions. Methods: The study is a prospective, single‐blind, RCT examining the effectiveness of an adjunctive individualized and manualized psychological intervention, compared with treatment as usual within youth‐specific early intervention services. The REsearch into COgnitive and behavioural VERsatility (RECOVER) intervention is delivered over a 6‐month period. About 122 young people in the early stages of BD‐I (at least one manic episode in the previous 2 years, with no more than five lifetime treated/untreated manic or hypomanic episodes) will be recruited. The assessments will occur at baseline, 3, 6 (primary endpoint, end of treatment), 9, 12, 15 and 18 months. Results: Recruitment will commence in January 2019 and is anticipated to occur over a 3.5‐year period. Conclusions: To date, there are no evidence‐based psychological therapies tailored to young people with early BD. We will test whether early psychological intervention in the course of BD can reduce the symptomatic, psychological, vocational and social impacts that are seen in entrenched disorder.